Lithium ion secondary battery, positive electrode slurry and power-consuming device

By introducing a first structural unit with weak polarity and a second structural unit with strong polarity into the polymer of a lithium-ion secondary battery, the problem of positive electrode slurry gel phenomenon is solved, dispersion and adhesion are improved, and the internal resistance of the battery is reduced.

CN119029156BActive Publication Date: 2025-03-04CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411443354.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-04
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The positive electrode slurry of lithium-ion secondary batteries is prone to gelation, resulting in uneven dispersion and increasing the internal resistance of the battery.

Method used

By introducing a weaker first structural unit and a second structural unit with strong polarity into the polymer of the lithium-ion secondary battery, the polarity of the polymer is regulated, the intermolecular force with the lithium-containing phosphate is weakened, and the dispersion and adhesion of the positive electrode slurry are improved.

Benefits of technology

The dispersion and adhesion of the positive electrode slurry are effectively improved, the diaphragm resistance of the positive electrode sheet is reduced, and the direct current internal resistance (DCR) of the lithium-ion secondary battery is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119029156B_ABST
    Figure CN119029156B_ABST
Patent Text Reader

Abstract

The present application relates to a lithium-ion secondary battery, a positive electrode slurry and an electrical device. The battery includes a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, the layer includes a polymer and a positive electrode active material including a lithium phosphate, the polymer includes a first structural unit and a second structural unit, the structural formula of the first structural unit includes, the structural formula of the second structural unit includes; the mass proportion of the first structural unit in the polymer is denoted as M1, 65%≤M1<100%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion secondary battery, a positive electrode slurry and an electrical device. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] In recent years, as the application scope of secondary batteries such as lithium-ion secondary batteries has become more and more extensive, lithium-ion secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion secondary batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.

[0004] The positive electrode active materials of lithium-ion secondary batteries include lithium iron phosphate, lithium cobalt oxide, etc. Compared with lithium cobalt oxide, lithium iron phosphate and other lithium-containing phosphates have the advantages of low price, better high temperature performance and safety. However, lithium iron phosphate and other lithium-containing phosphates are small in size, reaching the nanometer level, and the slurry dispersion is uneven and the slurry gel phenomenon will occur when preparing the positive electrode slurry. Summary of the invention

[0005] The present application provides a lithium ion secondary battery, a positive electrode slurry and an electrical device to improve the gel problem of the positive electrode slurry and reduce the internal resistance of the lithium ion secondary battery.

[0006] In a first aspect of the present application, a lithium-ion secondary battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material and a polymer, wherein the positive electrode active material comprises a lithium-containing phosphate, and wherein the polymer comprises a first structural unit and a second structural unit, wherein the structural formula of the first structural unit comprises , the structural formula of the second structural unit includes ;

[0007] Wherein, R1~R4 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, R5~R7 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene, anhydride, hydroxyl, carboxyl and carboxyl salt, R8 is selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene and metal cation, * represents the bonding position; the mass proportion of the first structural unit in the polymer is recorded as M1, and M1 satisfies: 65%≤M1<100%.

[0008] The average particle size of the lithium-containing phosphate in the positive electrode active material is usually relatively small. During the stirring process of the positive electrode slurry, the lithium-containing phosphate is easy to agglomerate, resulting in the positive electrode slurry being in a gel state. By introducing the first structural unit with a weaker polarity into the polymer of the above-mentioned lithium-ion secondary battery and controlling M1 within the above-mentioned range, the polarity of the polymer can be regulated, the intermolecular force between the polymer and the lithium-containing phosphate can be weakened, and the gel problem of the positive electrode slurry can be improved, so that the polymer can play a good dispersing role on the positive electrode active material in the positive electrode active material layer. The second structural unit has a strong polarity. Introducing the second structural unit into the polymer can make the polymer play a good bonding role on the positive electrode active material. Therefore, using a polymer containing the first structural unit and the second structural unit and controlling M1 within the above-mentioned range can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the film resistance of the positive electrode sheet, and further reducing the direct current internal resistance (DCR) of the lithium-ion secondary battery.

[0009] In some embodiments, the substituent groups in the substituted C1-C8 saturated alkyl, the substituted C3-C8 cycloalkyl, and the substituted heterocyclic alkylene in R5-R7 and R8 are independently selected from at least one of an ester group, a carbonyl group, an amide group, and an acid anhydride. Selecting the above-mentioned substituent groups can increase the polarity of the second structural unit, which is beneficial to improving the bonding effect of the polymer on the positive electrode active material.

[0010] In some embodiments, the metal cation includes at least one of a sodium ion and a potassium ion.

[0011] In some embodiments, the polymer further comprises a third structural unit, the structural formula of the third structural unit comprises , * represents the bonding position. The third structural unit can improve the bonding effect of the polymer on the positive electrode active material. The use of the polymer containing the first structural unit, the second structural unit and the third structural unit can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the film resistance of the positive electrode sheet, and further reducing the DCR of the lithium-ion secondary battery.

[0012] In some embodiments, the mass proportion of the first structural unit in the polymer is recorded as M1, and M1 satisfies: 70%≤M1≤90%. When M1 is within the above range, the polarity of the polymer can be reduced, and the dispersibility of the positive electrode active material can be further improved, thereby further reducing the film resistance of the positive electrode sheet and the DCR of the lithium-ion secondary battery.

[0013] In some embodiments, the mass proportion of the second structural unit in the polymer is recorded as M2, and the mass proportion of the third structural unit in the polymer is recorded as M3, and the M2 and M3 satisfy: 0<M2+M3≤35%, 0≤M3≤5%. M2 and M3 satisfy the above conditions, which can improve the adhesion of the polymer to the positive electrode active material, and is conducive to improving the adhesion and cohesion of the positive electrode sheet. Furthermore, 10%≤M2+M3≤30%.

[0014] In some embodiments, the polymer includes at least one of an olefin-acrylic acid copolymer, an olefin-acrylate copolymer, an olefin-acrylate copolymer grafted with maleic anhydride, an olefin-acrylate copolymer grafted with glycidyl methacrylate, an olefin-methacrylic acid-acrylate terpolymer, an olefin-acrylate-maleic anhydride terpolymer, an olefin-acrylate-glycidyl methacrylate terpolymer, an olefin-acrylate-2-octenyl succinic anhydride terpolymer, an olefin-acrylate-(2-methyl-2-propylene) succinic anhydride terpolymer, and an ethylene-propylene-diene rubber-acrylate copolymer.

[0015] In some embodiments, the olefin includes at least one of ethylene, propylene, and 1-butene.

[0016] In some embodiments, the acrylic acid ester includes at least one of methyl acrylate, ethyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-hexyl acrylate, and isooctyl acrylate.

[0017] Selecting the above-mentioned types of polymers can improve the gel problem of the positive electrode slurry, while improving the stability of the positive electrode slurry, which is beneficial to further improve the dispersion uniformity of the positive electrode active material.

[0018] In some embodiments, the weight average molecular weight of the polymer is 50,000 to 500,000. Such a design can further improve the dispersion effect of the polymer on the positive electrode active material, while taking into account the adhesion of the polymer to the positive electrode active material, which is conducive to further reducing the film resistance of the positive electrode sheet and the DCR of the positive electrode sheet.

[0019] In some embodiments, the mass proportion of the polymer in the positive electrode active material layer is 0.5% to 2%. Controlling the mass proportion of the polymer in the positive electrode active material layer within the above range can improve the adhesion of the polymer to the positive electrode active material, thereby further improving the adhesion and cohesion of the positive electrode sheet. Furthermore, the mass proportion of the polymer in the positive electrode active material layer is 1% to 1.8%.

[0020] In some embodiments, the lithium-containing phosphate comprises a chemical formula of Li m A a Fe x D d P y E e O z G g A comprises at least one element selected from the group consisting of Al, Na, K and Mg; D comprises at least one element selected from the group consisting of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti and V; E comprises at least one element selected from the group consisting of B, S, Si and N; G comprises at least one element selected from the group consisting of S, F, Cl and Br; wherein 0.5≤m≤1.5; 0≤a≤0.1; 0.5≤x≤1; 0≤d≤0.5; 0.5≤y≤1; 0≤e≤0.5; 3.5≤z≤4; and 0≤g≤0.5.

[0021] In a second aspect of the present application, a positive electrode slurry is provided, wherein the positive electrode slurry comprises a positive electrode active material, a polymer and a solvent, wherein the positive electrode active material comprises a lithium-containing phosphate, and the polymer comprises a first structural unit and a second structural unit, wherein the structural formula of the first structural unit comprises , the structural formula of the second structural unit includes ;

[0022] Wherein, R1~R4 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, R5~R7 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene, anhydride, hydroxyl, carboxyl and carboxyl salt, R8 is selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene and metal cation, * represents the bonding position; the mass proportion of the first structural unit in the polymer is recorded as M1, and M1 satisfies: 65%≤M1<100%.

[0023] By introducing the first structural unit with weak polarity into the polymer of the above-mentioned positive electrode slurry and controlling M1 within the above-mentioned range, the polarity of the polymer can be regulated, the intermolecular force between the polymer and the lithium-containing phosphate can be weakened, the gel problem of the positive electrode slurry can be improved, and the polymer can play a good dispersing role on the positive electrode active material. The second structural unit has a strong polarity. Introducing the second structural unit into the polymer can make the polymer play a good bonding role on the positive electrode active material. Therefore, using a polymer containing the first structural unit and the second structural unit and controlling M1 within the above-mentioned range can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the membrane resistance of the positive electrode sheet, and further reducing the DCR of the lithium-ion secondary battery.

[0024] In some embodiments, the substituent groups in the substituted C1-C8 saturated alkyl, the substituted C3-C8 cycloalkyl, and the substituted heterocyclic alkylene in R5-R7 and R8 are independently selected from at least one of an ester group, a carbonyl group, an amide group, and an acid anhydride. Selecting the above-mentioned substituent groups can increase the polarity of the second structural unit, which is beneficial to improving the bonding effect of the polymer on the positive electrode active material.

[0025] In some embodiments, the metal cation includes at least one of a sodium ion and a potassium ion.

[0026] In some embodiments, the polymer further comprises a third structural unit, the structural formula of the third structural unit comprises , * represents the bonding position. The third structural unit can improve the bonding effect of the polymer on the positive electrode active material. The use of the polymer containing the first structural unit, the second structural unit and the third structural unit can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the film resistance of the positive electrode sheet, and further reducing the DCR of the lithium-ion secondary battery.

[0027] In some embodiments, the solvent and the M1 satisfy one of the following conditions (1) or (2):

[0028] (1) 65%≤M1<80%, the solvent comprises at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide and acetone;

[0029] (2) 80%≤M1<100%, the solvent comprises at least one of solvent oil, pentylbenzene and petroleum ether.

[0030] By using different M1s, the polymer can be used in combination with different types of solvents, which can improve the solubility of the polymer in the corresponding solvent and further promote the uniformity of dispersion of the positive electrode slurry.

[0031] A third aspect of the present application provides an electrical device comprising the lithium-ion secondary battery described in the first aspect of the present application.

[0032] The electric device of the present application includes the lithium ion secondary battery provided by the present application, and thus has at least the same advantages as the lithium ion secondary battery.

[0033] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0035] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0036] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0037] Figure 3 It is a schematic diagram of a battery module according to one embodiment of the present application.

[0038] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application.

[0039] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0040] Figure 6 A schematic diagram of an electrical device using a lithium-ion secondary battery according to an embodiment of the present application as a power source.

[0041] Description of reference numerals:

[0042] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION

[0043] Below, some embodiments of the lithium-ion secondary battery, positive electrode slurry and power device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0044] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0045] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0046] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0047] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0048] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0049] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "comprise", etc., unless otherwise specified, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. Unless otherwise specified, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A not only includes a1, a2 and a3, but also includes other members". In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0050] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0051] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0052] The term "alkyl" refers to a saturated hydrocarbon containing a primary (normal) carbon atom, or a secondary carbon atom, or a tertiary carbon atom, or a quaternary carbon atom, or a combination thereof. A phrase containing the term, for example, "C1~C8 alkyl" refers to an alkyl containing 1 to 8 carbon atoms, and each occurrence can be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl or C8 alkyl. Suitable examples include, but are not limited to: methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu , s-butyl, -CH(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3 )CH(CH3)2), 3-methyl-1-butyl (-CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3) 2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH(CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2).

[0053] The term "alkylene" refers to a hydrocarbon group having two monovalent radical centers derived from an alkyl group by removing a hydrogen atom, which may be a saturated branched alkyl group or a saturated straight-chain alkyl group. For example, "C1-C8 alkylene" means that the alkyl portion contains 1 to 8 carbon atoms, and each occurrence may be independently C1 alkylene, C4 alkylene, C5 alkylene, C6 alkylene, C7 alkylene, C8 alkylene or C9 alkylene. Suitable examples include, but are not limited to, methylene (-CH2-), 1,1-ethyl (-CH(CH3)-), 1,2-ethyl (-CH2CH2-), 1,1-propyl (-CH(CH2CH3)-), 1,2-propyl (-CH2CH(CH3)-), 1,3-propyl (-CH2CH2CH2-) and 1,4-butyl (-CH2CH2CH2CH2-).

[0054] The term "cycloalkyl" refers to a non-aromatic hydrocarbon containing ring carbon atoms, which can be a monocyclic alkyl, a spirocyclic alkyl, or a bridged cycloalkyl. Phrases containing this term, for example, "C3~C8 cycloalkyl" refers to a cycloalkyl containing 3~8 carbon atoms, which can be independently C3 cycloalkyl, C4 cycloalkyl, C5 cycloalkyl, C6 cycloalkyl, C7 cycloalkyl or C8 cycloalkyl at each occurrence. Suitable examples include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cycloheptyl. In addition, "cycloalkyl" can also contain one or more double bonds.

[0055] The term "heterocyclyl" refers to a non-aromatic monocyclic or bicyclic cycloalkyl group containing 3 to 8 atoms, wherein 1 to 6 carbon atoms in the ring are replaced by heteroatoms selected from O, S or N.

[0056] The term "heterocyclylalkylene" refers to an alkylene-heterocyclyl group attached through an alkylene moiety, wherein alkylene and heterocyclyl are as defined above.

[0057] In one embodiment of the present application, a lithium-ion secondary battery is provided, including a positive electrode plate, the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material and a polymer, the positive electrode active material includes a lithium-containing phosphate, the polymer includes a first structural unit and a second structural unit, the structural formula of the first structural unit includes , the structural formula of the second structural unit includes ;

[0058] Wherein, R1~R4 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, R5~R7 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene, anhydride, hydroxyl, carboxyl and carboxyl salt, R8 is selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene and metal cation, * represents the bonding position; the mass proportion of the first structural unit in the polymer is recorded as M1, and M1 satisfies: 65%≤M1<100%.

[0059] The average particle size of the lithium-containing phosphate in the positive electrode active material is usually relatively small. During the stirring process of the positive electrode slurry, the lithium-containing phosphate is easy to agglomerate, resulting in the positive electrode slurry being in a gel state. By introducing the first structural unit with a weaker polarity into the polymer of the above-mentioned lithium-ion secondary battery and controlling M1 within the above-mentioned range, the polarity of the polymer can be regulated, the intermolecular force between the polymer and the lithium-containing phosphate can be weakened, and the gel problem of the positive electrode slurry can be improved, so that the polymer can play a good dispersing role on the positive electrode active material in the positive electrode active material layer. The second structural unit has a strong polarity. Introducing the second structural unit into the polymer can make the polymer play a good bonding role on the positive electrode active material. Therefore, using a polymer containing the first structural unit and the second structural unit and controlling M1 within the above-mentioned range can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the film resistance of the positive electrode sheet, and further reducing the direct current internal resistance (DCR) of the lithium-ion secondary battery.

[0060] Specifically, M1 includes, but is not limited to, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95% or a range between any two of the foregoing.

[0061] In some embodiments, the substituent groups in the substituted C1-C8 saturated alkyl, substituted C3-C8 cycloalkyl, and substituted heterocyclic alkylene in R5-R7 and R8 are independently selected from at least one of an ester group, a carbonyl group, an amide group, and an acid anhydride. Selecting the above-mentioned substituent groups can increase the polarity of the second structural unit, which is beneficial to improving the bonding effect of the polymer on the positive electrode active material.

[0062] In some embodiments, the metal cation includes at least one of a sodium ion and a potassium ion.

[0063] In some embodiments, the polymer further comprises a third structural unit, the structural formula of the third structural unit comprises , * represents the bonding position. The third structural unit can improve the bonding effect of the polymer on the positive electrode active material. The use of the polymer containing the first structural unit, the second structural unit and the third structural unit can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the film resistance of the positive electrode sheet, and further reducing the DCR of the lithium-ion secondary battery.

[0064] In some embodiments, 70%≤M1≤90%. When M1 is within the above range, the polarity of the polymer can be reduced, and the dispersibility of the positive electrode active material can be further improved, thereby further reducing the film resistance of the positive electrode sheet and the DCR of the lithium-ion secondary battery.

[0065] In some embodiments, the mass proportion of the second structural unit in the polymer is recorded as M2, and the mass proportion of the third structural unit in the polymer is recorded as M3, and M2 and M3 satisfy: 0<M2+M3≤35%, 0≤M3≤5%. M2 and M3 satisfy the above conditions, which can improve the adhesion of the polymer to the positive electrode active material, and is beneficial to improve the adhesion and cohesion of the positive electrode sheet. It can be understood that when M3=0, M2 satisfies: 0<M2≤35%. Specifically, M2 includes but is not limited to: 5%, 10%, 15%, 20%, 25%, 30%, 35% or a range between any two of the foregoing, and M3 includes but is not limited to: 0, 1%, 2%, 3%, 4%, 5% or a range between any two of the foregoing.

[0066] In some embodiments, 10%≤M2+M3≤30%. Such a design can further improve the adhesion of the polymer to the positive electrode active material, which is beneficial to further improve the adhesion and cohesion of the positive electrode sheet.

[0067] In some embodiments, the polymer has at least one of the structures shown in Formula I and Formula II below:

[0068] Formula I;

[0069] Formula II;

[0070] Wherein, 65%≤n1 / (n1+n2)<100%, 65%≤n3 / (n3+n4+n5)<100%, 0<(n4+n5) / (n3+n4+n5)≤35%, n1~n5 are each independently a positive integer, R9~R 16 Each is independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, R 17 ~R 19 , R 21 ~R 23 and R 25 ~R 27Each is independently selected from any one of hydrogen, substituted or unsubstituted C1-C8 saturated alkyl, substituted or unsubstituted C3-C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene, anhydride, hydroxyl, carboxyl and carboxyl salt, R 20 , R 24 and R 28 Each is independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclyl alkylene and metal cation.

[0071] Such a design can reduce the polarity of the polymer and further improve the dispersibility of the positive electrode active material, thereby further reducing the membrane resistance of the positive electrode sheet and the DCR of the lithium-ion secondary battery. At the same time, it can improve the adhesion of the polymer to the positive electrode active material, which is beneficial to improving the adhesion and cohesion of the positive electrode sheet.

[0072] In some embodiments, 70%≤n1 / (n1+n2)≤90%, 70%≤n3 / (n3+n4+n5)≤90%, and 10%≤(n4+n5) / (n3+n4+n5)≤30%.

[0073] In some embodiments, the polymer includes at least one of an olefin-acrylic acid copolymer, an olefin-acrylate copolymer, an olefin-acrylate copolymer grafted with maleic anhydride, an olefin-acrylate copolymer grafted with glycidyl methacrylate, an olefin-methacrylic acid-acrylate terpolymer, an olefin-acrylate-maleic anhydride terpolymer, an olefin-acrylate-glycidyl methacrylate terpolymer, an olefin-acrylate-2-octenyl succinic anhydride terpolymer, an olefin-acrylate-(2-methyl-2-propylene) succinic anhydride terpolymer, and an EPDM rubber-acrylate copolymer.

[0074] In some embodiments, the olefin comprises at least one of ethylene, propylene and 1-butene. Alternatively, the olefin is ethylene.

[0075] In some embodiments, the acrylic acid ester includes at least one of methyl acrylate, ethyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-hexyl acrylate, and isooctyl acrylate.

[0076] Selecting the above-mentioned types of polymers can improve the gel problem of the positive electrode slurry, while improving the stability of the positive electrode slurry, which is beneficial to further improve the dispersion uniformity of the positive electrode active material.

[0077] In some embodiments, the weight average molecular weight of the polymer is 50,000 to 500,000. Such a design can further improve the dispersion effect of the polymer on the positive electrode active material, while taking into account the adhesion of the polymer to the positive electrode active material, which is conducive to further reducing the film resistance of the positive electrode sheet and the DCR of the positive electrode sheet. Specifically, the weight average molecular weight of the polymer includes but is not limited to: 50,000, 100,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, 500,000 or a range between any two of the foregoing.

[0078] Without limitation, the weight average molecular weight of the polymer can be determined by gel chromatography. For example: use a 0.1% polystyrene solution sample as a reference and select a matching chromatographic column. Use purified N-methylpyrrolidone (NMP) solvent to prepare a 5% test solution, and let the prepared solution stand for one day for use. During the test, first use a syringe to draw tetrahydrofuran, rinse, and repeat several times. Then draw 5mL of the experimental solution, remove the air in the syringe, and wipe the needle tip dry. Finally, slowly inject the sample solution into the injection port. After the indication stabilizes, obtain the data and read the weight average molecular weight.

[0079] In some embodiments, the polymer includes a blend of a first polymer and a second polymer, the weight average molecular weight of the first polymer is 50,000 to 200,000, and the weight average molecular weight of the second polymer is 300,000 to 500,000. The first polymer can improve the dispersibility of the positive electrode active material, and the second polymer can improve its bonding effect on the positive electrode active material. The first polymer and the second polymer are used in combination, so that the polymer has a good dispersing effect on the positive electrode active material while improving the bonding of the polymer to the positive electrode active material, which is beneficial to further reduce the film resistance of the positive electrode sheet and the DCR of the positive electrode sheet. As a non-limiting example, the weight average molecular weight of the first polymer can be 50,000, and the weight average molecular weight of the second polymer can be 500,000; or the weight average molecular weight of the first polymer can be 150,000, and the weight average molecular weight of the second polymer can be 300,000; or the weight average molecular weight of the first polymer can be 200,000, and the weight average molecular weight of the second polymer can be 450,000.

[0080] In some embodiments, the first polymer and the second polymer are each independently selected from at least one of olefin-acrylic acid copolymer, olefin-acrylate copolymer, maleic anhydride grafted olefin-acrylate copolymer, methacrylate glycidyl grafted olefin-acrylate copolymer, olefin-methacrylic acid-acrylate terpolymer, olefin-acrylate-maleic anhydride terpolymer, olefin-acrylate-methacrylate glycidyl terpolymer, olefin-acrylate-2-octenyl succinic anhydride terpolymer, olefin-acrylate-(2-methyl-2-propylene) succinic anhydride terpolymer and EPDM-acrylate copolymer. The first polymer and the second polymer may be polymers of the same type with different weight average molecular weights or may be polymers of different types. As a non-limiting example, the first polymer may be an olefin-acrylic acid copolymer with a weight average molecular weight of 50,000, and the second polymer may be an olefin-acrylic acid copolymer with a weight average molecular weight of 500,000; or the first polymer may be an olefin-acrylic acid copolymer with a weight average molecular weight of 500,000, and the second polymer may be an olefin-acrylate copolymer grafted with maleic anhydride with a weight average molecular weight of 500,000. For example: the first polymer is an ethylene-acrylic acid copolymer with a weight average molecular weight of 50,000, and the second polymer can be an ethylene-acrylic acid copolymer with a weight average molecular weight of 500,000; or the first polymer can be an ethylene-acrylic acid copolymer with a weight average molecular weight of 50,000, and the second polymer can be an ethylene-methyl acrylate copolymer grafted with maleic anhydride with a weight average molecular weight of 500,000.

[0081] In some embodiments, the polymer includes only the third polymer, and the weight average molecular weight of the third polymer is 200,000 to 500,000. Such a design can make the polymer have a good dispersion effect on the positive electrode active material, while improving the adhesion of the polymer to the positive electrode active material, which is conducive to further reducing the film resistance of the positive electrode sheet and the DCR of the positive electrode sheet.

[0082] In some embodiments, the polymer includes only the third polymer, and the weight average molecular weight of the third polymer is 300,000 to 400,000. Such a design can make the polymer have a good dispersion effect on the positive electrode active material, while improving the adhesion of the polymer to the positive electrode active material, which is conducive to further reducing the film resistance of the positive electrode sheet and the DCR of the positive electrode sheet.

[0083] In some embodiments, the third polymer is selected from at least one of olefin-acrylic acid copolymers, olefin-acrylate copolymers, maleic anhydride-grafted olefin-acrylate copolymers, glycidyl methacrylate-grafted olefin-acrylate copolymers, olefin-methacrylic acid-acrylate terpolymers, olefin-acrylate-maleic anhydride terpolymers, olefin-acrylate-glycidyl methacrylate terpolymers, olefin-acrylate-2-octenyl succinic anhydride terpolymers, olefin-acrylate-(2-methyl-2-propylene) succinic anhydride terpolymers and ethylene-propylene rubber-acrylate copolymers.

[0084] In some embodiments, the mass proportion of the polymer in the positive electrode active material layer is 0.5% to 2%. Controlling the mass proportion of the polymer in the positive electrode active material layer within the above range can improve the adhesion of the polymer to the positive electrode active material, thereby further improving the adhesion and cohesion of the positive electrode sheet. Specifically, the above mass proportion includes but is not limited to: 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2% or a range between any two of the foregoing.

[0085] In some embodiments, the mass proportion of the polymer in the positive electrode active material layer is 1% to 1.8%. With this design, the bonding force and cohesion of the positive electrode sheet are improved while the mass proportion of the polymer in the positive electrode active material layer is relatively small, thereby improving the energy density of the lithium-ion secondary battery.

[0086] In some embodiments, the lithium-containing phosphate includes a chemical formula of Li m A a Fe x D d P y E e O z G g A includes at least one element selected from the group consisting of Al, Na, K and Mg; D includes at least one element selected from the group consisting of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti and V; E includes at least one element selected from the group consisting of B, S, Si and N; G includes at least one element selected from the group consisting of S, F, Cl and Br; wherein, 0.5≤m≤1.5; 0≤a≤0.1; 0.5≤x≤1; 0≤d≤0.5; 0.5≤y≤1; 0≤e≤0.5; 3.5≤z≤4; and 0≤g≤0.5.

[0087] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode plate is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode active material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode active materials is also within the scope of positive electrode active materials. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include coating modification.

[0088] In the list of positive electrode active materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.

[0089] As a non-limiting example, the lithium-containing phosphate may include a chemical formula of Li m A a Fe x D d P y E e O z G g Considering the chemical formula Li m A a Fe x D d P y E e O z G g The material has a weak conductivity and is usually m A a Fe x D d P y E e O z G g The surface of the material is coated with carbon to improve its conductivity.

[0090] In some embodiments, the positive electrode sheet further includes a positive electrode current collector, and the positive electrode active material layer is disposed on at least one surface of the positive electrode current collector.

[0091] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0092] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0093] In some embodiments, the positive electrode active material layer may further optionally include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0094] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the polymer described above in the present application, and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode current collector, and after drying, cold pressing, etc., the positive electrode sheet can be obtained. The surface of the positive electrode current collector coated with the positive electrode slurry can be on a single surface of the positive electrode current collector or on both surfaces of the positive electrode current collector.

[0095] In some embodiments, the lithium ion secondary battery further includes a negative electrode sheet, the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer disposed on at least one surface of the negative electrode collector, the negative electrode active material layer includes a negative electrode active material.

[0096] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0097] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0098] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0099] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0100] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0101] In some embodiments, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0102] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%-60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s-10000mPa·s.

[0103] In some embodiments, the lithium-ion secondary battery further includes an electrolyte, which has the function of conducting ions between the positive electrode plate and the negative electrode plate. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid.

[0104] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0105] In some embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP).

[0106] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, )、ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate ( ), fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0107] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0108] In some embodiments, the additive in the electrolyte may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0109] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0110] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0111] In some embodiments, the isolation film has a thickness of 6 μm-40 μm, and optionally 12 μm-20 μm.

[0112] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0113] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0114] In some embodiments, the outer packaging of the lithium ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0115] A lithium-ion secondary battery includes at least one battery cell. A lithium-ion secondary battery may include one or more battery cells.

[0116] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0117] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0118] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.

[0119] The lithium-ion secondary battery may be a battery module 4 or a battery pack 1 .

[0120] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.

[0121] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0122] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0123] In some embodiments, the battery modules described above may also be assembled into a battery pack. The number of battery modules contained in the battery pack may be one or more. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0124] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0125] Another embodiment of the present application provides a positive electrode slurry, which includes a positive electrode active material, a polymer and a solvent, wherein the positive electrode active material includes a lithium-containing phosphate, and the polymer includes a first structural unit and a second structural unit. The structural formula of the first structural unit includes , the structural formula of the second structural unit includes ;

[0126] Wherein, R1~R4 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, R5~R7 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene, anhydride, hydroxyl, carboxyl and carboxyl salt, R8 is selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene and metal cation, * represents the bonding position; the mass proportion of the first structural unit in the polymer is recorded as M1, and M1 satisfies: 65%≤M1<100%.

[0127] By introducing the first structural unit with weak polarity into the polymer of the above-mentioned positive electrode slurry and controlling M1 within the above-mentioned range, the polarity of the polymer can be regulated, the intermolecular force between the polymer and the lithium-containing phosphate can be weakened, the gel problem of the positive electrode slurry can be improved, and the polymer can play a good dispersing role on the positive electrode active material. The second structural unit has a strong polarity. Introducing the second structural unit into the polymer can make the polymer play a good bonding role on the positive electrode active material. Therefore, using a polymer containing the first structural unit and the second structural unit and controlling M1 within the above-mentioned range can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the membrane resistance of the positive electrode sheet, and further reducing the DCR of the lithium-ion secondary battery.

[0128] In some embodiments, the substituent groups in the substituted C1-C8 saturated alkyl, substituted C3-C8 cycloalkyl, and substituted heterocyclic alkylene in R5-R7 and R8 are independently selected from at least one of an ester group, a carbonyl group, an amide group, and an acid anhydride. Selecting the above-mentioned substituent groups can increase the polarity of the second structural unit, which is beneficial to improving the bonding effect of the polymer on the positive electrode active material.

[0129] In some embodiments, the metal cation includes at least one of a sodium ion and a potassium ion.

[0130] In some embodiments, the polymer further comprises a third structural unit, the structure of the third structural unit comprising , * represents the bonding position. The third structural unit can improve the bonding effect of the polymer on the positive electrode active material. The use of the polymer containing the first structural unit, the second structural unit and the third structural unit can not only improve the dispersibility of the positive electrode slurry, but also make the bonding and stability of the positive electrode sheet good, thereby reducing the film resistance of the positive electrode sheet, and further reducing the DCR of the lithium-ion secondary battery.

[0131] In some embodiments, the solvent and M1 satisfy one of the following conditions (1) or (2):

[0132] (1) 65%≤M1<80%, the solvent in the positive electrode slurry includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide and acetone;

[0133] (2) 80%≤M1<100%, the solvent in the positive electrode slurry includes at least one of solvent oil, pentylbenzene and petroleum ether.

[0134] By using different M1s, the polymer can be used in combination with different types of solvents, which can improve the solubility of the polymer in the corresponding solvent and further promote the uniformity of the dispersion of the positive electrode slurry. The solvent oil includes but is not limited to: one or more of D20 solvent oil, D40 solvent oil, D60 solvent oil, D80 solvent oil, D100 solvent oil, D120 solvent oil and D200 solvent oil.

[0135] Another embodiment of the present application provides an electrical device, comprising the lithium-ion secondary battery mentioned above.

[0136] Lithium-ion secondary batteries can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0137] As an electrical device, a lithium-ion secondary battery can be selected according to its usage requirements.

[0138] Figure 6The power consumption device 6 is taken as an example. The power consumption device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery pack or a battery module can be used.

[0139] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.

[0140] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0141] Example 1

[0142] (1) Preparation of positive electrode sheet:

[0143] (1.1) Prepare the polymer according to the following preparation method:

[0144] (1.1.1) Add the emulsifier sodium dodecyl sulfate into a beaker containing deionized water, stir at 500 rpm to dissolve it, then add methyl acrylate monomer and maleic anhydride monomer, stir at 800 rpm for 2 h at 50°C to obtain a mixed solution;

[0145] (1.1.2) Add the mixed solution to a reaction kettle replaced with ethylene gas, add initiator dibenzoyl peroxide (the total amount of initiator accounts for 0.5% of the total mass of the reaction monomers), introduce ethylene gas (the mass ratio of ethylene monomer a, methyl acrylate monomer b and maleic anhydride monomer c is a:b:c=80:18:2), heat and stir, and keep the pressure of the system constant. When the temperature rises to 70°C, keep the temperature and pressure to react for 4 hours;

[0146] (1.1.3) After the reaction is completed, the reaction liquid is poured into a methanol solution containing a trace amount of hydroquinone to demulsify. When the precipitate no longer increases, it is filtered by suction, and the upper filter cake is taken and dried to obtain an ethylene-methyl acrylate-maleic anhydride terpolymer (polymer);

[0147] In the obtained polymer, the first structural unit is derived from ethylene, the second structural unit is derived from methyl acrylate, and the third structural unit is derived from maleic anhydride. The mass proportions of the first structural unit, the second structural unit and the third structural unit in the polymer are M1, M2, and M3, respectively, which are approximately 80%, 18%, and 2%, and the weight average molecular weight of the polymer is 398,000.

[0148] The first structural unit is shown in formula III, the second structural unit is shown in formula IV, and the third structural unit is shown in formula V:

[0149] Formula III;

[0150] Formula IV;

[0151] Formula V.

[0152] (1.2) Ethylene-methyl acrylate-maleic anhydride terpolymer (polymer) is dissolved in solvent oil D80 as a binder to obtain a binder solution, and then the positive electrode active material lithium iron phosphate LiFePO4 (LFP), the conductive agent carbon black (Super P) and the binder solution are mixed to obtain a positive electrode slurry; the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P) and the above polymer in the positive electrode slurry is 98.1:0.4:1.5. The positive electrode slurry is coated on the double-sided surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0153] (2) Preparation of negative electrode sheet:

[0154] The negative electrode active material graphite, the thickener sodium carboxymethyl cellulose, the binder styrene butadiene rubber and the conductive agent acetylene black are mixed in a mass ratio of 97:1:1:1, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the double-side surface of the copper foil; the copper foil is dried at room temperature and then transferred to a 120°C oven for drying for 1 hour, and then cold pressed and cut to obtain the negative electrode sheet.

[0155] (3) Isolation film:

[0156] A 12μm thick polypropylene isolation film was selected.

[0157] (4) Preparation of electrolyte:

[0158] The organic solvent is a mixed solution containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 20:20:60. In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt LiPF6 is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L.

[0159] (5) Preparation of batteries:

[0160] The positive electrode sheet, the negative electrode sheet and the isolation film are made into an electrode assembly through a winding process. The isolation film is placed between the positive and negative electrode sheets to play an isolating role. The aluminum-plastic film is then loaded and baked at 80°C to remove water. The electrolyte is then injected and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a lithium-ion secondary battery is obtained.

[0161] Embodiment 2~5

[0162] The preparation of the lithium ion secondary battery is basically the same as in Example 1, except that: the mass ratio of ethylene monomer a, methyl acrylate monomer b and maleic anhydride monomer c in step (1.1.2) is changed to a:b:c, thereby changing the mass proportion of the first structural unit in the polymer, as described in Table 1;

[0163] In Example 2, a:b:c=65:33:2;

[0164] In Example 3, a:b:c=70:28:2;

[0165] In Example 4, a:b:c=90:8:2;

[0166] In Example 5, a:b:c=95:3:2.

[0167] Example 6

[0168] The preparation of the lithium-ion secondary battery is basically the same as in Example 1, except that the heat preservation and pressure preservation reaction time in step (1.1.2) is changed, thereby changing the weight average molecular weight of the polymer, as described in Table 1.

[0169] Embodiments 7 to 10

[0170] The preparation of the lithium-ion secondary battery is basically the same as in Example 1, except that: the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P) and the polymer in the positive electrode slurry in step (1.2) is changed, that is, the mass proportion of the polymer in the positive electrode active material layer is changed, as described in Table 1;

[0171] In Example 7, the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P) and the polymer in the positive electrode slurry is 99.1:0.4:0.5;

[0172] In Example 8, the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P) and the polymer in the positive electrode slurry is 98.6:0.4:1;

[0173] In Example 9, the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P) and the polymer in the positive electrode slurry is 97.2:0.4:1.8;

[0174] In Example 10, the mass ratio of the positive electrode active material LFP, the conductive agent carbon black (Super P) and the polymer in the positive electrode slurry is 97.6:0.4:2.

[0175] Embodiment 11

[0176] The preparation of the lithium ion secondary battery is basically the same as in Example 1, except that the type of polymer prepared in step (1.1) is changed, as described in Table 1;

[0177] In Example 11, the polymer was prepared as follows:

[0178] (1.1.1) Add the emulsifier sodium dodecyl sulfate into a beaker containing deionized water, stir at 500 rpm to dissolve it, then add methyl acrylate monomer, stir at 800 rpm at 50°C for 2 h to obtain a mixed solution;

[0179] (1.1.2) Add the mixed solution to a reaction kettle that has been replaced with ethylene gas, add initiator dibenzoyl peroxide (the total amount of initiator accounts for 0.5% of the total mass of the reaction monomers), introduce ethylene gas (the mass ratio of ethylene monomer a to methyl acrylate monomer b is a:b=85:10), heat and stir, and keep the pressure of the system constant. When the temperature rises to 70°C, keep the temperature and pressure to react for 4 hours;

[0180] (1.1.3) After the reaction is completed, the reaction liquid is poured into a methanol solution containing a trace amount of hydroquinone to break the emulsion. When the precipitate no longer increases, it is filtered by suction, and the upper filter cake is taken and dried to obtain ethylene-methyl acrylate copolymer;

[0181] (1.1.4) Weigh ethylene-methyl acrylate copolymer and glycidyl methacrylate (the mass ratio of ethylene a and glycidyl methacrylate c is a:c=85:5) and place them in xylene. Stir under nitrogen atmosphere until they are completely dissolved. Weigh a certain amount of dibenzoyl peroxide (the mass is 0.5% of the total mass of ethylene-acrylate copolymer and glycidyl methacrylate monomer) and dissolve it in xylene. Slowly add it dropwise to the reactor and react at 90°C for 5 hours.

[0182] (1.1.5) The post-reaction solution is poured into anhydrous ethanol, the grafted product is precipitated and separated, filtered under reduced pressure, and impurities are washed away with acetone, and then vacuum dried to constant weight to obtain ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate (polymer), wherein the mass proportion of the grafted group derived from glycidyl methacrylate in the polymer is about 5%, and the weight average molecular weight of the ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate is 411,000.

[0183] Example 12

[0184] The preparation of the lithium ion secondary battery is basically the same as in Example 1, except that the type of polymer prepared in step (1.1) is changed, as described in Table 1;

[0185] In Example 12, the polymer was prepared as follows:

[0186] (1.1.1) Add the emulsifier sodium dodecyl sulfate into a beaker containing deionized water, stir at 500 rpm to dissolve it, then add methyl acrylate monomer, stir at 800 rpm at 50°C for 2 h to obtain a mixed solution;

[0187] (1.1.2) Add the mixed solution to a reaction kettle that has been replaced with ethylene gas, add initiator dibenzoyl peroxide (the total amount of initiator accounts for 0.5% of the total mass of the reaction monomers), introduce ethylene gas (the mass ratio of ethylene monomer a to methyl acrylate monomer b is a:b=85:10), heat and stir, and keep the pressure of the system constant. When the temperature rises to 70°C, keep the temperature and pressure to react for 4 hours;

[0188] (1.1.3) After the reaction is completed, the reaction liquid is poured into a methanol solution containing a trace amount of hydroquinone to break the emulsion. When the precipitate no longer increases, it is filtered by suction, and the upper filter cake is taken and dried to obtain ethylene-methyl acrylate copolymer;

[0189] (1.1.4) Weigh ethylene-methyl acrylate copolymer and maleic anhydride (the mass ratio of ethylene a and maleic anhydride c is a:c=85:5) and place them in xylene. Stir them under nitrogen atmosphere until they are completely dissolved. Weigh a certain amount of dibenzoyl peroxide (the mass is 0.5% of the total mass of ethylene-acrylate copolymer and maleic anhydride monomer) and dissolve it in xylene. Slowly add it dropwise into the reactor and react at 90°C for 5 hours.

[0190] (1.1.5) The post-reaction solution was poured into anhydrous ethanol, and the grafted product was precipitated and separated, filtered under reduced pressure, and impurities were washed away with acetone, and then vacuum dried to constant weight to obtain maleic anhydride grafted ethylene-methyl acrylate copolymer (polymer), wherein the grafted group derived from maleic anhydride accounts for about 5% by mass in the polymer, and the weight average molecular weight of the maleic anhydride grafted ethylene-methyl acrylate copolymer is 384,000.

[0191] In Example 11, the mass proportion of the grafted groups derived from glycidyl methacrylate in the ethylene-methyl acrylate copolymer grafted with glycidyl methacrylate, and in Example 12, the mass proportion of the grafted groups derived from maleic anhydride in the ethylene-methyl acrylate copolymer grafted with maleic anhydride can be obtained by chemical titration. For example, for Example 12, an alkaline substance such as sodium hydroxide solution can be used to react off the grafted groups derived from maleic anhydride in the ethylene-methyl acrylate copolymer grafted with maleic anhydride, and the mass proportion of the grafted groups derived from maleic anhydride in the copolymer can be obtained based on the consumption of the alkaline substance.

[0192] Embodiment 13

[0193] The preparation of the lithium ion secondary battery is basically the same as in Example 1, except that the type of polymer prepared in step (1.1) is changed, as described in Table 1;

[0194] In Example 13, the polymer was prepared as follows:

[0195] (1.1.1) Add the emulsifier sodium dodecyl sulfate into a beaker containing deionized water, stir at 500 rpm to dissolve it, then add the acrylic acid monomer, stir at 800 rpm at 50°C for 2 h to obtain a mixed solution;

[0196] (1.1.2) Add the mixed solution to a reaction kettle that has been replaced with ethylene gas, add initiator dibenzoyl peroxide (the total amount of initiator accounts for 0.5% of the total mass of the reaction monomers), introduce ethylene gas (the mass ratio of ethylene monomer a to acrylic acid monomer b is a:b=85:15), heat and stir, and keep the pressure of the system constant. When the temperature rises to 70°C, keep the temperature and pressure to react for 4 hours;

[0197] (1.1.3) After the reaction is completed, the reaction liquid is poured into a methanol solution containing a trace amount of hydroquinone to demulsify. When the precipitate no longer increases, it is filtered by suction, and the upper filter cake is taken and dried to obtain an ethylene-acrylic acid copolymer (polymer);

[0198] In the obtained polymer, the first structural unit is derived from ethylene, and the second structural unit is derived from acrylic acid. The mass proportions M1 and M2 of the first structural unit and the second structural unit in the polymer are approximately 85% and 15%, respectively, and the weight average molecular weight of the polymer is 406,000.

[0199] Embodiment 14

[0200] The preparation of the lithium ion secondary battery is basically the same as in Example 1, except that the type of polymer prepared in step (1.1) is changed, as described in Table 1;

[0201] In Example 14, the polymer was prepared as follows:

[0202] (1.1.1) Add the emulsifier sodium dodecyl sulfate into a beaker containing deionized water, stir at 500 rpm to dissolve it, then add n-butyl acrylate monomer, stir at 800 rpm at 50°C for 2 h to obtain a mixed solution;

[0203] (1.1.2) Add the mixed solution to a reaction kettle that has been replaced with ethylene gas, add initiator dibenzoyl peroxide (the total amount of initiator accounts for 0.5% of the total mass of the reaction monomers), introduce ethylene gas (the mass ratio of ethylene monomer a to n-butyl acrylate monomer b is a:b=85:15), heat and stir, and keep the pressure of the system constant. When the temperature rises to 70°C, keep the temperature and pressure to react for 4 hours;

[0204] (1.1.3) After the reaction is completed, the reaction liquid is poured into a methanol solution containing a trace amount of hydroquinone to demulsify. When the precipitate no longer increases, it is filtered by suction, and the upper filter cake is taken and dried to obtain an ethylene-n-butyl acrylate copolymer (polymer);

[0205] In the obtained polymer, the first structural unit is derived from ethylene, and the second structural unit is derived from n-butyl acrylate. The mass proportions M1 and M2 of the first structural unit and the second structural unit in the polymer are approximately 85% and 15%, respectively, and the weight average molecular weight of the polymer is 403,000.

[0206] Comparative Example 1

[0207] The preparation of the lithium-ion secondary battery is basically the same as in Example 1, except that: ethylene gas is not introduced in step (1.1.2), and the mass ratio of methyl acrylate monomer b to maleic anhydride monomer c is b:c=98:2, so that the obtained methyl acrylate-maleic anhydride copolymer (polymer) does not contain the first structural unit, the mass proportion of the second structural unit is about 98%, and the mass proportion of the third structural unit is about 2%, as described in Table 1.

[0208] Test Case

[0209] (1) Cathode slurry status test

[0210] Prepare 500 mL of fresh positive electrode slurry, seal the fresh positive electrode slurry in the beaker with plastic wrap, let it stand for 2 hours, 4 hours or 48 hours, open the plastic wrap, and gently move the surface of the slurry with a steel ruler to check the state of the slurry.

[0211] The gel state is divided into the following levels:

[0212] ① Mild gel: The slurry has a certain fluidity, but there are obvious slight lumps of gel falling from the slurry at the end of the ruler.

[0213] ② Moderate gel: The slurry has relatively poor fluidity, with obvious lumps of jelly, which appear in lumps when picked up.

[0214] ③ Heavy gel: The slurry has no fluidity and is jelly-like; the slurry is solid, has no fluidity, and can be picked up in one piece.

[0215] (2) Adhesion test of positive electrode

[0216] The positive electrode sheets prepared in each embodiment are cut into test samples of 20mm×100mm size for later use; one side of the double-sided tape is adhered to the surface of the steel plate, and the other side is adhered to one side of the electrode sheet to be tested, and compacted with a pressure roller to make it completely fit with the electrode sheet; one end of the current collector is bent in the opposite direction with a bending angle of 180°; a high-speed rail tensile testing machine is used for testing, one end of the steel plate is fixed to the lower fixture of the tensile testing machine, and the bent end of the current collector is fixed to the upper fixture, the angle of the current collector is adjusted to ensure that the upper and lower ends are in a vertical position, and then the sample is stretched at a speed of 50mm / min until the positive electrode active material layer is completely peeled off from the surface of the current collector, and the displacement and force in the process are recorded, and the force when the force is balanced is taken as the bonding force of the electrode sheet, and the bonding strength is taken as the force divided by the adhesion length of the sample, that is, the bonding force of the positive electrode sheet.

[0217] (3) Cohesion test of positive electrode

[0218] The positive electrode sheets prepared in each embodiment are cut into test samples of 20mm×100mm size for later use; one side of the double-sided tape is adhered to the surface of the steel plate, and the other side is adhered to one side of the sheet to be tested, and compacted with a roller to make it completely fit with the sheet; a special tape for cohesion test is adhered to the other side of the sheet and compacted with a roller; one end of the special tape for cohesion is bent in reverse with a bending angle of 180°; a high-speed rail tensile testing machine is used for testing, one end of the steel plate is fixed to the clamp below the tensile testing machine, the bent end of the current collector is fixed to the upper clamp, the angle of the current collector is adjusted to ensure that the upper and lower ends are in a vertical position, and then the sample is stretched at a speed of 50mm / min until the current collector is completely peeled off from the surface of the current collector, the displacement and force in the process are recorded, the force when the force is balanced is taken as the bonding force of the sheet, and the force divided by the adhesion length of the sample is taken as the bonding strength, that is, the cohesion of the positive electrode sheet.

[0219] (4) Battery DCR test:

[0220] At 25°C, charge the battery to 3.6V at 0.33C, then charge at constant voltage until the current is ≤0.05C, and record the capacity at this time as 90% SOC. After 5 minutes of standing, discharge the battery at a constant current rate of 0.33C to a capacity of 50% SOC. After adjustment, test the battery voltage and record it as V1. Discharge the battery at a constant current rate of 4C (corresponding current is recorded as I) for 10s, and test the battery voltage after the discharge, and record it as V2; DC internal resistance DCR=(V1−V2) / I.

[0221] The product parameters and test results of each embodiment and comparative example are shown in Tables 1 and 2. In Tables 1 and 2, " / " represents the absence of the substance or parameter.

[0222] Table 1

[0223]

[0224]

[0225] In Table 1, M1 represents the mass proportion of the first structural unit in the polymer, M2 represents the mass proportion of the second structural unit in the polymer, and M3 represents the mass proportion of the third structural unit in the polymer.

[0226] Table 2

[0227]

[0228] Since the positive electrode slurry of Comparative Example 1 was severely gelled after standing for 2 hours, it could not be used for mass production of positive electrode sheets. Therefore, the bonding strength and cohesion of the positive electrode sheets of Comparative Example 1 were not tested.

[0229] It can be seen from Table 2 that, compared with Comparative Example 1, the gel problem of the positive electrode slurries of Examples 1 to 14 is significantly improved, the bonding force and cohesion of the positive electrode sheets are good, and the DCR of the battery is low, indicating that the introduction of the first structural unit with weaker polarity into the polymers of Examples 1 to 14 can effectively improve the dispersibility of the positive electrode active material in the positive electrode active material layer, and the second structural unit and the third structural unit in the polymer can make the bonding and stability of the positive electrode sheets good, and can reduce the DCR of the battery.

[0230] The above description of various embodiments tends to emphasize the differences between the various embodiments. The same or similar aspects can be referenced to each other, and for the sake of brevity, they will not be repeated herein.

[0231] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium ion secondary battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material and a polymer, wherein the positive electrode active material comprises a lithium-containing phosphate, and wherein the polymer comprises a first structural unit and a second structural unit, wherein the structural formula of the first structural unit comprises , the structural formula of the second structural unit includes ; Wherein, R1~R4 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, R5~R7 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene, anhydride, hydroxyl, carboxyl and carboxyl salt, R8 is selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene and metal cation, * represents a bonding position; the polymer further comprises a third structural unit, the structural formula of the third structural unit includes , * represents the bonding position; The mass proportion of the first structural unit in the polymer is recorded as M1, and M1 satisfies: 65%≤M1<100%; The mass proportion of the second structural unit in the polymer is recorded as M2, the mass proportion of the third structural unit in the polymer is recorded as M3, and the M2 and the M3 satisfy: 0<M2+M3≤35%, 0<M3≤5%.

2. The lithium ion secondary battery according to claim 1, characterized in that: The substituent groups in the substituted C1-C8 saturated alkyl, the substituted C3-C8 cycloalkyl and the substituted heterocyclic alkylene in R5-R7 and R8 are each independently selected from at least one of an ester group, a carbonyl group, an amide group and an acid anhydride; and / or, The metal cation includes at least one of a sodium ion and a potassium ion.

3. The lithium ion secondary battery according to claim 1, characterized in that: 70%≤M1≤90%。 4. The lithium ion secondary battery according to claim 3, characterized in that: 80%≤M1≤90%。 5. The lithium ion secondary battery according to claim 1, characterized in that: 10%≤M2+M3≤30%.

6. The lithium ion secondary battery according to claim 5, characterized in that: 10%≤M2+M3≤25%.

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that The polymer includes at least one of olefin-acrylic acid copolymer, olefin-acrylate copolymer, maleic anhydride grafted olefin-acrylate copolymer, glycidyl methacrylate grafted olefin-acrylate copolymer, olefin-methacrylic acid-acrylate terpolymer, olefin-acrylate-maleic anhydride terpolymer, olefin-acrylate-glycidyl methacrylate terpolymer, olefin-acrylate-2-octenyl succinic anhydride terpolymer, olefin-acrylate-(2-methyl-2-propylene) succinic anhydride terpolymer and ethylene-propylene rubber-acrylate copolymer.

8. The lithium ion secondary battery according to claim 7, characterized in that: The olefin comprises at least one of ethylene, propylene and 1-butene; and / or, The acrylic acid ester includes at least one of methyl acrylate, ethyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-hexyl acrylate and isooctyl acrylate.

9. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that The weight average molecular weight of the polymer is 50,000 to 500,000.

10. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that The polymer accounts for 0.5% to 2% by mass in the positive electrode active material layer.

11. The lithium ion secondary battery according to claim 10, characterized in that: The polymer accounts for 1% to 1.8% by mass in the positive electrode active material layer.

12. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The lithium-containing phosphate comprises a chemical formula of Li m A a Fe x D d P y E e O z G g A comprises at least one element selected from the group consisting of Al, Na, K and Mg; D comprises at least one element selected from the group consisting of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, Ti and V; E comprises at least one element selected from the group consisting of B, S, Si and N; G comprises at least one element selected from the group consisting of S, F, Cl and Br; wherein 0.5≤m≤1.5; 0≤a≤0.1; 0.5≤x≤1; 0≤d≤0.5; 0.5≤y≤1; 0≤e≤0.5; 3.5≤z≤4; and 0≤g≤0.

5.

13. A positive electrode slurry, characterized in that: The positive electrode slurry comprises a positive electrode active material, a polymer and a solvent, wherein the positive electrode active material comprises a lithium-containing phosphate, the polymer comprises a first structural unit and a second structural unit, and the structural formula of the first structural unit comprises , the structural formula of the second structural unit includes ; Wherein, R1~R4 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, R5~R7 are each independently selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene, anhydride, hydroxyl, carboxyl and carboxyl salt, R8 is selected from any one of hydrogen, substituted or unsubstituted C1~C8 saturated alkyl, substituted or unsubstituted C3~C8 cycloalkyl, substituted or unsubstituted heterocyclic alkylene and metal cation, * represents a bonding position; the polymer further comprises a third structural unit, the structural formula of the third structural unit includes , * represents the bonding position; The mass proportion of the first structural unit in the polymer is recorded as M1, and M1 satisfies: 65%≤M1<100%; The mass proportion of the second structural unit in the polymer is recorded as M2, the mass proportion of the third structural unit in the polymer is recorded as M3, and the M2 and the M3 satisfy: 0<M2+M3≤35%, 0<M3≤5%.

14. The positive electrode slurry according to claim 13, characterized in that: The substituent groups in the substituted C1-C8 saturated alkyl, the substituted C3-C8 cycloalkyl and the substituted heterocyclic alkylene in R5-R7 and R8 are each independently selected from at least one of an ester group, a carbonyl group, an amide group and an acid anhydride; and / or, The metal cation includes at least one of a sodium ion and a potassium ion.

15. The positive electrode slurry according to claim 13 or 14, characterized in that: 70%≤M1≤90% and / or, 10%≤M2+M3≤30%.

16. The positive electrode slurry according to claim 13 or 14, characterized in that: The solvent and the M1 satisfy one of the following conditions (1) or (2): (1) 65%≤M1<80%, the solvent comprises at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide and acetone; (2) 80%≤M1<100%, the solvent comprises at least one of solvent oil, pentylbenzene and petroleum ether.

17. An electrical device, characterized in that: A lithium ion secondary battery comprising the lithium ion secondary battery according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Method for manufacturing slurry for secondary battery positive electrodes, method for manufacturing positive electrode for secondary batteries, and secondary battery

    JP2015128012A